Program Pembelajaran Berbasis Kemaritiman Pada Satuan PAUD - Anggraini Anggraini; Gerni Ekasari; Siti Fatimah Bugis; Siti Rahmah Muhaena; Nadila M. Taher; Agustan Arifin (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Falahu Village is one of the villages in Sanana District, Sula Islands Regency which is the main target in PHP2D activities located in a very wide coastal area and has natural potential that can enable and support maritime-based learning processes. The aim of the maritime-based learning program is to help introduce teachers to PAUD units and the community in the Sula Islands Regency to the importance of maritime-based learning. By increasing Human Resources (HR) in the field of education and utilization of natural resources and providing knowledge to children through learning media and coastal APE. The implementation of activities is carried out in August-October 2021. The method of implementing Maritime-based learning program activities includes 3 stages, namely: Planning and preparation, implementation, and evaluation. The activity was carried out through socialization and seminars involving several teachers in the Sula Islands Regency area as well as involving villagers and the education office. Workhsop workshop activities aim to provide information, understanding, knowledge and skills to participants in the preparation of learning tools and maritime-based educational game tools. Participants in the Maritime-Based Learning Program are PAUD educators in the Coastal area of Sanana District. The results obtained during the activity were the support from the local government, especially the Education Office, the Falahu Village Head and the PAUD Heads in the Sanana sub-district. The success of this program can be obtained from the reflection results from filling out the questionnaire which shows that after participating in the activity participants can gain knowledge and experience in the preparation of learning tools, teacher interest in the application of maritime learning, as well as discovering new things in the manufacture of learning media and APE from potential natural.